Energy Security: The Irena Role in Supporting Net Zero Emissions Program of Indonesia - Luthfiani, Novera (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
This study examines how Indonesia's energy sustainability is affected by the International Renewable Energy Agency's (IRENA) efforts to increase energy security in the nation. In light of the pressing global concerns around climate change and Indonesia's expanding energy requirements, IRENA is essential in helping to ease the country's transition to a more reliable and sustainable energy system. IRENA helps Indonesia reduce its reliance on fossil fuels and increase the use of renewable energy by supporting cutting-edge technology and sustainable energy policies. In order to assess IRENA's contributions to national energy policy making, international cooperation, and the development of renewable energy technologies, this study uses a desk analysis approach. The results showed that Irena's role in assisting Indonesia in achieving Net Zero Emission through renewable energy has an influence on Indonesia's energy security.